2017
DOI: 10.1016/j.celrep.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

BAFF- and TACI-Dependent Processing of BAFFR by ADAM Proteases Regulates the Survival of B Cells

Abstract: B cell activating factor (BAFF) provides B cells with essential survival signals. It binds to three receptors: BAFFR, TACI, and BCMA that are differentially expressed by B cell subsets. BAFFR is early expressed in circulating B cells and provides key signals for further maturation. Here, we report that highly regulated BAFFR processing events modulate BAFF responses. BAFFR processing is triggered by BAFF binding in B cells co-expressing TACI and it is executed by the metalloproteases ADAM10 and ADAM17. The deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 52 publications
3
65
0
2
Order By: Relevance
“…One prominent example is the soluble tissue inhibitors of metalloproteases that (to various extent) block ADAM10, ADAM17, and MT‐MMPs (e.g., Amour et al , , ). Conversely, other ligands are known to induce shedding as observed for Notch, RGMa, BAFFR, and DDR1 (Pan & Rubin, ; Bozkulak & Weinmaster, ; van Tetering et al , ; van Erp et al , ; Shitomi et al , ; Smulski et al , ). An emerging layer of regulation is post‐translational modification at the substrate level.…”
Section: Regulation Of Sheddingmentioning
confidence: 99%
“…One prominent example is the soluble tissue inhibitors of metalloproteases that (to various extent) block ADAM10, ADAM17, and MT‐MMPs (e.g., Amour et al , , ). Conversely, other ligands are known to induce shedding as observed for Notch, RGMa, BAFFR, and DDR1 (Pan & Rubin, ; Bozkulak & Weinmaster, ; van Tetering et al , ; van Erp et al , ; Shitomi et al , ; Smulski et al , ). An emerging layer of regulation is post‐translational modification at the substrate level.…”
Section: Regulation Of Sheddingmentioning
confidence: 99%
“…Each receptor exhibits a unique expression pattern on distinct B cell subsets, in part accounting for differential functional roles during an immune response. 28 29). 25 All three of the BAFF/APRIL receptors can be shed from the cell surface by the activity of γ-secretase (BCMA) or ADAM proteases (BAFF-R and TACI).…”
Section: Baff Family Receptorsmentioning
confidence: 99%
“…28 and Jnk/p38 pathways to counteract apoptosis, drive immunoglobulin class switch recombination, and promote antibody production. 28 and Jnk/p38 pathways to counteract apoptosis, drive immunoglobulin class switch recombination, and promote antibody production.…”
Section: Baff Family Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Smulski et al recently reported that unlike TACI and BCMA, BAFF-R is not constitutively shed, and processing requires BAFF stimulation and TACI coexpression (45). Stimulation with a homotrimeric BAFF 3-mer, which triggers BAFF-R but not TACI (46), activates ADAM10 to cleave and release BAFF-R from the membrane in the presence of TACI.…”
Section: Introductionmentioning
confidence: 99%